Assessment for Learning Practices among Outstanding Science Teachers during the COVID-19 Pandemic: A Case Study in the Sultanate of Oman - Al-Khaburi, Sajda Ahmad Abdullah; Al-Hosni, Huda Ali Said (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to study Assessment for Learning practices. The study group was a sample of three teachers working in an international school in Muscat. The study was conducted in the 2020/2021 academic year. To achieve the objectives of this study, an observation card an interview were designed. The apparent authenticity of the tool was verified by presenting it to a group of specialized arbitrators at Sultan Qaboos University. The results of the study obtained the importance of having a safe learning environment and to apply strategies so Assessment for Learning practices can work successfully. The study recommends to plan well to apply Assessment for Learning practices and differentiation.
Keywords: Assessment for learning; Outstanding Science Teachers; Covid -19; case study